A golden era for Open Access or a trend towards the golden road to Open Access? - Pieper, Dirk (Septentrio Conference Series, 2014)
When looking at the „Dramatic Growth of Open Access“[1] it seems that we live in a golden era for Open Access (OA). From a library point of view one could notice a trend to the golden road to OA. The German Research Foundation (DFG) started the support programme „Open Access Publishing“[2] in 2010 with the overall goal, to help universities to establish long-lasting and reliable structures for paying OA publications which demand article processing charges. The recent discussion about the Finch Report[3] shows the precariousness about the role of publishers, and libraries fear about escalating costs again, if OA moves mainly towards the golden road. This presentation explaines the DFG programme and highlights the experiences of Bielefeld University Library (UL) within and concludes, that riding on the golden road is not the only way for libraries, to support universities making their publication output as visible as possible. Bielefeld UL started the support of OA publications with paying article processing charges back in 2004 with a BioMed Central membership and introduced a publication funds in 2008. In 2011 and 2012 the publication funds is supported by the above mentioned DFG programme. Besides the conventional questions like building a helpdesk for OA or how to organise the process from requesting money for OA publications by university members until the payment of article fees it became clear, that it is important to determine the publications of Bielefeld University as much as possible. The common publisher tools can only capture a part of the overall publication output of a university. Thus, the main focus of Bielefeld UL within the DFG programme lies on the integration of funding, detection and the enhancement of outside publicity of publications. Further on, Bielefeld University decided not to support hybrid OA publications anymore. For the next step, Bielefeld UL plans to install a clearing centre for OA at Bielefeld University. The now established system PUB (Publications at Bielefeld University) gives the UL a more valid basis than „Web of Science“ or „SCOPUS“ when trying to estimate the possible costs for golden OA. From the perspective of increasing the visibilty of Bielefeld University publications as much as possible and from the perspective of economic costs alone the OA strategy Bielefeld UL will include supporting the green road in the future as well. [1] Heather Morrison, http://poeticeconomics.blogspot.ca/ [2] http://www.dfg.de/formulare/12_20/12_20.pdf [3] http://www.researchinfonet.org/wp-content/uploads/2012/06/Finch-Group-report-executive-summary-FINAL-VERSION.pdf